2018
DOI: 10.1007/s10826-018-1236-8
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validity of the Eyberg Child Behavior Inventory with Taiwanese Clinic-Referred Children

Abstract: The Eyberg Child Behavior Inventory (ECBI) has previously been shown to be a psychometrically sound instrument used to assess disruptive behaviors in children in the United States and in other cultures/countries but not in Taiwan. The purpose of this study was to examine the factor structure and to establish the discriminative validity of the ECBI with two groups of Taiwanese children: 70 clinic-referred children with clinically elevated externalizing behavior problems and 70 community-based matched comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Information regarding the mean frequency of each Intensity Scale item, which highlights how often a certain disruptive behavior occurs, and the percentage of each Problem Scale item that caregivers rated as a problem in Table 2 is important for Taiwanese researchers and clinicians to know, as it helps to better understand which child behaviors are developmentally appropriate and which are clinically elevated based on caregivers’ reports. Previous research also has demonstrated adequate internal consistency, convergent and divergent validity with the CBCL Externalizing Scale, discriminative validity, and five-and six-factor structures of the ECBI in clinically referred Taiwanese children and their matched peers (Chen & Fortson, 2015; Chen, Fortson, & Tiano, under review). Future studies are needed to examine the test-retest reliability in Taiwanese families.…”
Section: Discussionmentioning
confidence: 94%
“…Information regarding the mean frequency of each Intensity Scale item, which highlights how often a certain disruptive behavior occurs, and the percentage of each Problem Scale item that caregivers rated as a problem in Table 2 is important for Taiwanese researchers and clinicians to know, as it helps to better understand which child behaviors are developmentally appropriate and which are clinically elevated based on caregivers’ reports. Previous research also has demonstrated adequate internal consistency, convergent and divergent validity with the CBCL Externalizing Scale, discriminative validity, and five-and six-factor structures of the ECBI in clinically referred Taiwanese children and their matched peers (Chen & Fortson, 2015; Chen, Fortson, & Tiano, under review). Future studies are needed to examine the test-retest reliability in Taiwanese families.…”
Section: Discussionmentioning
confidence: 94%